2009
DOI: 10.1021/ja901574c
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Potassium Responsive Nanochannel: G-Quadruplex DNA Conformational Switching in a Synthetic Nanopore

Abstract: Potassium is especially crucial in modulating the activity of muscles and nerves whose cells have specialized ion channels for transporting potassium. Normal body function extremely depends on the regulation of potassium concentrations inside the ion channels within a certain range. For life science, undoubtedly, it is significant and challenging to study and imitate these processes happening in living organisms with a convenient artificial system. Here we report a novel biomimetic nanochannel system which has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
267
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 323 publications
(275 citation statements)
references
References 58 publications
5
267
0
3
Order By: Relevance
“…[13][14][15][16][17][18][19] Recent advances concerning the fabrication processes and the tailoring of the surface properties have permitted to control the pore geometry [20][21][22][23] and the response to external stimuli such as voltage, 24,25 temperature, 26,27 pH [28][29][30] or the presence of a given analyte in the pore solution. [31][32][33][34] These features have allowed the fabrication of nanofluidic devices [35][36][37][38] with potential applications in sensing, 34,39,40 energy harvesting 41,42 and information processing.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Recent advances concerning the fabrication processes and the tailoring of the surface properties have permitted to control the pore geometry [20][21][22][23] and the response to external stimuli such as voltage, 24,25 temperature, 26,27 pH [28][29][30] or the presence of a given analyte in the pore solution. [31][32][33][34] These features have allowed the fabrication of nanofluidic devices [35][36][37][38] with potential applications in sensing, 34,39,40 energy harvesting 41,42 and information processing.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of oligonucleotides, proton, 393,394 metal ions, 395 and metal complexes 396 were used as the fuel. In order to drive the systems, however, "photo-isomerization" is undoubtedly more preferable, since no raw materials are wasted and no byproducts are formed.…”
Section: Determination Of Dna Nanostructures In Solutionsmentioning
confidence: 99%
“…To understand the transportation mechanism and behavior of ions, biomolecules in the pore/channel and polymer and inorganic nanopores/nanochannels have been created. To confer on these nanopores/nanochannels stimuliresponsive properties to mimic their natural models, polymers [35,36], peptides [37] and DNA [38][39][40] have been modified onto the inner surface of nanopores/nanochannels. Among these studies, DNA has been demonstrated as an outstanding molecule to create an intelligent nanopore/nanochannel because of the clear transformation of secondary structure.…”
Section: Dna Responsive Nanopore/nanochannelmentioning
confidence: 99%
“…The nanopore/nanochannel has a pH-responsive conductivity change and the authors proposed that the mechanism was related to the charge densities of different DNA conformations. One year later, Hou et al [40] further studied the response mechanisms of DNAmodified nanopore/nanochannel with a potassium ion responding to a DNA sequence that is guanine (G) rich, and can fold into a four-stranded G-quadruplex in the presence of potassium ions. In the presence of lithium, they demonstrated that the G-rich sequences adopted a loosely packed single-stranded structure inside the channel (Figure 4).…”
Section: Dna Responsive Nanopore/nanochannelmentioning
confidence: 99%
See 1 more Smart Citation